Why Place Really Matters: A Qualitative Approach to Housing Preferences and Neighborhood Effects. Issue 4 (4th July 2017) - Shelby, Hayden
Abstract: The idea that a person's neighborhood or zip code can predict his or her life outcomes has motivated a host of housing policies aimed at redressing racial segregation and breaking up areas of concentrated poverty. This article critically examines underlying assumptions about high-poverty neighborhoods that motivate those policies. Using ethnographic methods, I present the location preferences of residents living in a low-income neighborhood in Columbus, Ohio, and show the ways in which their perceptions of their neighborhood run counter to common portrayals. This analysis provides clues as to why the underlying logic of dispersal and mobility may be flawed. I conclude that place matters very much to people living in this neighborhood, just not in the way commonly implied by dispersal and mobility policy advocates. The implication is that stability, rather than mobility, ought to be the focus of more housing discussions.